PHYSICO-CHEMICAL BASIS OF CLARIFIED WATER TO THE THIN-LAYER SETTLERS - , О. В. (Municipal economy of cities. Series: «Economy science», 2013)
The physical and chemical bases of clarification of water in thin landfill.